JOURNALISM AND FACT-CHECKING: typification of sources used for checking and criteria for selecting fact-checked material – an analysis by Agência Lupa and Aos Fatos - Damasceno, Daniel de Rezende (2020)
Fact-checking was initially used to verify the factuality of information given by political agents. However, the proliferation of false information on social networks and concerns about the political use of spreading lies have led to fact-checking methodologies also being used to combat fake news. In terms of a cognitive and behavioral approach, Lazer et al. (2018) suggest there are some doubts as to how effective this methodology is. This article analyzes the performance of two Brazilian checking agencies, Aos Fatos and Agência Lupa. We demonstrate that, although checking discourse is directly related to the credibility of organizations, the agencies themselves do not lay out the criteria for selecting what is to be checked. The platforms that use this form of fact-checking mainly rely on data and studies provided by official sources and public institutions, once again compromising the credibility of the process.A prática de fact-checking foi iniciada para verificar a factualidade das informações nos discursos de agentes políticos. Mas a proliferação de informações falsas nas redes sociais da internet, e a preocupação com a disseminação de mentiras como instrumento político, fez com que as metodologias de fact-checking também fossem utilizadas para combater fake news. Levando em consideração uma abordagem cognitiva e comportamental, Lazer et al. (2018) alertam que existem dúvidas quanto à eficácia dessa utilização. Esse artigo analisa a atuação de duas agências brasileiras de checagem, Aos Fatos e Agência Lupa. Demonstramos que, apesar da checagem de discursos ter relação direta com a credibilidade das organizações, as próprias agências não explicitam os critérios que orientam a seleção do que é checado. E que nessa modalidade de checagem, as plataformas de fact-checking se valem, sobretudo, de dados e estudos fornecidos por fontes oficiais e instituições públicas, comprometendo mais uma vez a credibilidade do processo.La práctica de fact-checking inició para verificar la factualidad de las informaciones en los discursos de agentes políticos. Pero la proliferación de informaciones falsas en las redes sociales de internet, y la preocupación por la diseminación de mentiras como instrumento político, hizo que las metodologías de fact-checking también fueran utilizadas para combatir las fake news. Teniendo en cuenta un enfoque cognitivo y conductual, Lazer et al. (2018) advierten que existen dudas sobre la eficacia de esta utilización. Este artículo analiza la actuación de dos agencias brasileñas de chequeo, Aos Fatos y Agência Lupa. Demostramos que, aunque la verificación del discurso tiene una relación directa con la credibilidad de las organizaciones, las agencias mismas no detallan los criterios que guían la selección de lo que se verifica. Y que en este modo de verificación, las plataformas de verificación de hechos se basan principalmente en datos y estudios proporcionados por fuentes oficiales e instituciones públicas, comprometiendo una vez más la credibilidad del proceso.